Inducible factors and interaction of pulmonary fibrosis induced by prenatal dexamethasone exposure in offspring rats. (15th April 2022) - Zhang, Ziyao; Chen, Huijun; Yu, Pengxia; Ge, Caiyun; Fang, Man; Zhao, Xiaoqi; Geng, Qing; Wang, Hui
Highlights: This study revealed a correlation between prenatal dexamethasone exposure and susceptibility to pulmonary fibrosis. This study showed a gender difference with respect to susceptibility to pulmonary fibrosis in the rat. There were interactions between prenatal dexamethasone exposure and ovariectomy. Abstract: This study aimed to investigate the correlation between prenatal dexamethasone exposure (PDE) and susceptibility to pulmonary fibrosis in offspring. Healthy female Wistar rats were given dexamethasone (0.2 mg/kg.d) or an equal volume of normal saline subcutaneously from 9 to 20 days after conception. Some of their female offspring underwent ovariectomy (OV) at 22 weeks after birth. All animals were euthanized at 28 weeks after birth. The morphological changes related to pulmonary fibrosis and extracellular matrix-related gene expression were detected, and Two-way ANOVA analyzed the interaction between PDE and OV. The results showed that adult offspring rats in FD group (female rats with PDE treatment) had early pulmonary fibrosis changes, such as pulmonary interstitial thickening, and increased expression of type IV collagen (COL4), α -smooth muscle actin (α-SMA) and fibronectin (FN) in lung tissues compared with those in FC group (female rats with saline treatment). In addition, adult offspring rats in FDO group (female rats with PDE and OV treatment) showed signs of pulmonary fibrosis, including apparent extracellular matrix deposition, increased lung injury scores ( P ＜0.01, P ＜0.05), and extracellular matrix related gene expression ( P ＜0.01, P ＜0.05), compared with rats in FDS (female rats with PDE treatment alone) or rats in FCO group (female rats with OV treatment alone). Moreover, PDE and OV had an interactive effect on the development of pulmonary fibrosis in female adult offspring. This study first reported the correlation between PDE and susceptibility to pulmonary fibrosis in female offspring rats, as well as the synergistic effect of PDE and OV in this pathological event, which provided a basis for further understanding of the pathogenesis of fetal originated pulmonary fibrosis.